The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/1809-4422asoc0250r1vu18l3ao
|View full text |Cite
|
Sign up to set email alerts
|

The Amazon Beyond the Forests, Rivers and Schools: Social Representations and Environmental Problems

Abstract: The Amazon has historically been represented as a terrestrial paradise in social imaginaries. However, over recent decades, it has been converted into a complex subject with a number of dilemmas to be solved. This study sought to gain an insight into the social representations of environmental problems and the impacts of these problems on the daily lives of teachers working in Castanhal, the State of Pará, Brazil. It uses a theoretical and methodological framework based on Social Representation Theory and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…When interpreting the SR of rural and urban settlers within the framework of the socioenvironmental conflict characterized by the complexity of its social, economic, cultural and environmental components, it was possible to identify the meaning constructed by the stakeholders from their subjectivity when interacting with the territory and the environment 89 , 98 . Additionally, it was concluded that the appreciations that result from intersubjectivity in group exchanges are related to social identity and are transmitted in daily life by means of inherited traditions, expressions, emotions, knowledge and beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…When interpreting the SR of rural and urban settlers within the framework of the socioenvironmental conflict characterized by the complexity of its social, economic, cultural and environmental components, it was possible to identify the meaning constructed by the stakeholders from their subjectivity when interacting with the territory and the environment 89 , 98 . Additionally, it was concluded that the appreciations that result from intersubjectivity in group exchanges are related to social identity and are transmitted in daily life by means of inherited traditions, expressions, emotions, knowledge and beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Technological and economic changes have caused several social impacts in the Amazon region. Some examples are cited by [120], such as the construction of the Trans-Amazonian Highway in 1974, the increase in the price of agricultural products, the implementation of hydroelectric plants, mining activities, and port-related activities. This suggests that new accident prevention projects including the implementation of new technologies or devices, such as those for improving navigation activities, should be evaluated considering the social inequalities in different Amazon regions.…”
Section: Social Relevancementioning
confidence: 99%
“…In the empirical field, this study deals with a regional reality marked by conflicts related to sustainability, different from other approaches that investigated national or international contexts. The research was carried out in the Amazon Region of Brazil, seeking to verify how economic conflicts are associated with social and environmental demands in their various aspects, as identity constituent elements of their communities' lifestyles (Andrade, 2018).…”
Section: Introductionmentioning
confidence: 99%